2014
DOI: 10.19030/tlc.v11i4.8851
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary Analysis Of Interteachings Frequent Examinations Component In The Community College Classroom

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 16 publications
0
16
0
Order By: Relevance
“…Rather, they reported only once to the laboratory and took the quiz”; Saville et al, 2005 , p. 162) or were alternative interventions, such as attending traditional lectures or completing anagrams (e.g., Saville et al, 2014 ). Pre- versus post-comparisons (two within-subjects designs) either investigated a single group comparing a change in outcome measures (e.g., examination scores; Felderman, 2014 ) or compared pre- versus post-changes in two groups, including a control group (e.g., interteaching versus traditional lecture on examination scores; Slezak & Faas, 2017 ). The eleven studies that reported implementation of SCMs (e.g., alternating-treatment designs; Felderman, 2016 ; Gayman et al, 2018 ) were included in the between-groups meta-analyses in a similar approach to that reported by Zelinsky and Shadish ( 2018 ) because the data reported in them were already aggregated per courses, groups and/or sections (i.e., no individual/single-case data were available).…”
Section: Methodsmentioning
confidence: 99%
“…Rather, they reported only once to the laboratory and took the quiz”; Saville et al, 2005 , p. 162) or were alternative interventions, such as attending traditional lectures or completing anagrams (e.g., Saville et al, 2014 ). Pre- versus post-comparisons (two within-subjects designs) either investigated a single group comparing a change in outcome measures (e.g., examination scores; Felderman, 2014 ) or compared pre- versus post-changes in two groups, including a control group (e.g., interteaching versus traditional lecture on examination scores; Slezak & Faas, 2017 ). The eleven studies that reported implementation of SCMs (e.g., alternating-treatment designs; Felderman, 2016 ; Gayman et al, 2018 ) were included in the between-groups meta-analyses in a similar approach to that reported by Zelinsky and Shadish ( 2018 ) because the data reported in them were already aggregated per courses, groups and/or sections (i.e., no individual/single-case data were available).…”
Section: Methodsmentioning
confidence: 99%
“…Ideally, instructors will arrange multiple assessment opportunities throughout the course as this gives students frequent opportunities to demonstrate what they have learned, identify and correct any learning deficits, and minimize the impact that poor performance during any one specific assessment has on the final course grade. In addition, having frequent assessment opportunities can improve long-term retention of information (Felderman 2014;Bangert-Drowns et al 2016;Saville et al 2014). To reinforce participation during interteaching, questions on quizzes and exams should be connected to material on preparation guides and clarifying lectures (Bernstein and Chase 2013).…”
Section: Interteachingmentioning
confidence: 99%
“…Interteaching is a relatively new behavioral approach to college instruction in which contingencies are arranged in support of frequent student engagement and peer-to-peer collaboration, and lectures are reduced to a supportive, supplementary role (Gayman et al, 2018 , 2020 ). In addition to producing better learning outcomes (for reviews, see Hurtado-Parrado et al, 2021 ; Querol et al, 2015 ; Saville et al, 2011 ; Sturmey et al, 2015 ), students have reported interteaching to be more enjoyable (Querol et al, 2015 ; Saville et al, 2011 ), and interteaching has been shown to improve long-term retention (Felderman, 2014 ; Saville et al, 2014 ). Last, interteaching offers unique benefits to instructors, who have reported interteaching class preparation to be less time-consuming than traditional teaching formats (Sturmey et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…Probes may include any style question so long as they target material from prep guides. Further, it is recommended that they be conducted frequently and routinely (Felderman, 2014 ). Another empirically supported method for promoting learning and retention is the use of cumulative exams (Khanna et al, 2013 ; Lawrence, 2013 ).…”
Section: Introductionmentioning
confidence: 99%